AN INVESTIGATION INTO CONSUMER PURCHASE INTENTIONS FOR ECO-FRIENDLY PRODUCTS: ANALYZING AGE AND GENDER DIFFERENCES - Batbaatar Chuluunbaatar; Ugtakhjargal Baldangombo2, (Journal of Business and Innovation (Бизнес & Инноваци), 2024)
The main aim of this study is to investigate the factors that influence a consumer’s intention to purchase environmentally sustainable products, with particular attention to the interplay of age and gender demographics. Precisely, the study probes a spectrum of influences, including consumers’ attitudes, subjective norms, environmental knowlegde, eco-labeling, and willingness to pay a premium price for eco-conscious products. We examined the sources from which consumers learn about eco-friendly products and the elements that drive their green purchasing decisions. The study showed significant differences in consumer attitudes, environmental awareness and eco-labels by gender, while willingness to pay higher prices and willingness to purchase green products differed by age group. Among the 5 hypotheses proposed in the study, the hypothesis that environmental knowledge has a positive effect on the intention to purchase green products was rejected.